Analysis of Law Making No.48/2009 on Judicial Power using Jutidic, Sociological, and Philosophical Analysis - Rio Marshel Sahertian (Universitas Muhammadiyah Surakarta, 2024)
Since its enactment, this law has been the subject of in-depth analysis to understand the impact and implications on the life of the nation and state. In this paper, we will describe the analysis of Law No.48/2009 In addition, the role and responsibility of the community in supporting the implementation of this Law is also the focus of analysis. Through philosophical analysis, we can assess the extent to which the Act is consistent with the basic values and principles of the rule of law. Juridical Analysis opens insight into legal aspects that need to be evaluated and improved. Sociological analysis provides an overview of how these regulations are accepted and implemented by society. In conclusion, an indepth analysis of Law No. From a juridical perspective, this law, in theory, has a positive impact by affirming judicial autonomy. In a philosophical view, the law reflects the basic principles of the rule of law, but an evaluation of its implementation shows that these values have not been fully reflected in the day-to-day practice of justice. The existence of conceptual problems in the substance of Law No. Controversies during the formation of this law created challenges in implementing the law, especially in the context of the election of Supreme Court justices.